Sustainable tourism development strategy by SWOT analysis: Boujagh National Park, Iran - Reihanian, A.; Mahmood, N.Z.; Kahrom, E.; Hin, T.W. (2012)
This paper explores the applicability of transforming the current state of tourism in Boujagh National Park (BNP) (a region located in the northern Iran with an area of 3177. ha) to a sustainable tourism model. To plan and implement this, different management and decision making tools were used including interviews and questionnaire surveys as well as SWOT analysis. A series of interviews was conducted in order to identify actions taken by governmental bodies responsible (e.g., Department of Environment). In addition, the visitors of the park were surveyed to assess the rate of fulfillment of sustainable tourism development in the park. Local residents were also taken into account by using a survey to reveal the problems and attractions of the park. Results showed that the existing tourism activities in the park did not conform to sustainability requirements. Thus, a SWOT analysis was used to identify the required management strategies to improve the tourism in the park. Â© 2012 Elsevier Ltd.